Virginity for Sale II: Queering Latina Heterosexuality in America’s Next Top Virginity Auction. - Dunn, Jennifer C.; Vik, Tennley A. (Sexuality & Culture, 2018)
In July 2014, we published our rhetorical analysis of the online discourses surrounding a young woman, Natalie Dylan, announcing an auction for her virginity through the Moonlite Bunny Ranch, a legal Nevada brothel, in Sexuality and Culture. Although Dylan did not follow through with her auction she still earned at least $125,000. Given the potential financial gain involved, is it any surprise that another virginity auction would follow? The Moonlite Bunny Ranch announced the “America’s Next Top Bunny Ranch Virgin” competition on their websites in 2015 and introduced the only contestant, Katherine Stone. For this paper, we conducted a critical rhetorical analysis of websites announcing her auction, Stone’s YouTube video explaining her motives, and online discourses that followed. Unlike Dylan, who claimed a third wave feminist perspective that emphasized her right to choose what to do with her own body as well as a right to profit from it, Stone explains, instead, her selfless motivation: she is doing it out of love for her family. Our analysis suggests the public discourses focus on her agency only insofar as she “chose” to auction off her virginity. However, these messages also focus on Stone’s motives—sacrificing for her family and providing for her own self-improvement. Taking into consideration the seemingly contradictory discourses that characterize Stone as both passive and active, self-sacrificing and ambitious, and the virgin and the whore, we suggest that the discourses surrounding her auction queer Latina heterosexuality.